Linseed breeding for early maturing and dual-purpose genotypes in North-Western Himalayas: LINSEED BREEDING FOR EARLY MATURING AND DUAL-PURPOSE GENOTYPES IN HIMALAYAS - ASHITA BISHT; SATISH PAUL (Journal of Oilseeds Research, 2019)
Performance of linseed genotypes and hybrids in a series of crosses following line × tester mating design was studied for 13 agro-morphological traits involving parents having fibre, seed and dual-types. A total of 15 lines (7 indigenous and 8 exotic) and three well-adapted, early maturing indigenous testers were used for generation of new variability. Although both additive and non-additive gene effects were significant, the non-additive gene action coupled with the presence of low heritability predominated for all the traits. Genotypes Baner, Belinka and JLS-73 were the most promising parents. The highest value of heterobeltiosis and standard heterosis was observed for seed yield (226.62%) and primary branches (263.66%) per plant respectively. Based on per se performance, SCA effects and extent of heterosis the cross-combination KL-284 × JLS-73 was the most promising for dual-purpose. However, for earliness and other seed yield and related traits Ottawa × RLC-133 was the most pr